Journal Packing Density across Subject Disciplines among BRICS Countries : A Study - Singh, Shivendra; Pandita, Ramesh K (DESIDOC Journal of Library & Information Technology, 2018)
The study attempts to assess the journal packing density (JPD) of the research journals published across Brazil, Russia, India, China and South Africa (BRICS) countries during 2013-2015. The JPD of the research journals has been computed on the basis of volume. The study covers 27 main subject disciplines and the JPD has been calculated against each individual subject discipline. 2499 research journals were identified as indexed by the Scopus from the BRICS countries, constituting 6.92 per cent of total research journals indexed by the Scopus all across the world. China is the leading country from the BRICS league to have the maximum 914 (36.57%) research journals. The average JPD of the research journals published across BRICS nations is 132.77 research articles per journal per volume, which is far greater than the average global JPD of 101.84 research articles. On average 92.55 research journals are published across BRICS countries in each subject discipline. Physics and astronomy, engineering, and energy are the three leading subject disciplines among BRICS nations having maximum JPD of 209.52, 191.40, and 190.08 research articles per journal per volume. Apart from these, there are various other facts which have come to the fore about the prevailing trend of JPD among BRICS nations.